2021
DOI: 10.21037/jgo-20-599
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of neoadjuvant PD-1 inhibitor with chemotherapy for locally advanced esophageal squamous cell carcinoma

Abstract: Background: Neoadjuvant therapy followed by esophagectomy has been recognized as an effective treatment for locally advanced esophageal cancer, though still has a dismal prognosis. Antibodies against programmed death 1 (PD-1) protein improve survival in patients with advanced or metastatic esophageal squamous cell carcinoma (ESCC) compared with chemotherapy in second-line therapy. However, neoadjuvant PD-1 inhibitor combined with chemotherapy has not been tested in locally advanced ESCC.We conducted this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
100
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 31 publications
11
100
3
Order By: Relevance
“…Another study recently presented at ESMO congress 2020 employed a similar regimen comprising nab-paclitaxel/S1 plus toripalimab for preoperative treatment of a similar population, but their pCR rate (16.67%) was much lower than ours, which could possibly be explained by the fact that their cohort received only two courses of treatment before surgery while our entire cohort was subjected to 3 cycles of treatment (24). In another study conducted by Shen et al, the pCR elicited by neoadjuvant PD-1 plus chemotherapy was 33%, which was exactly the same as ours (25). Actually, our study does differ from theirs.…”
supporting
confidence: 74%
“…Another study recently presented at ESMO congress 2020 employed a similar regimen comprising nab-paclitaxel/S1 plus toripalimab for preoperative treatment of a similar population, but their pCR rate (16.67%) was much lower than ours, which could possibly be explained by the fact that their cohort received only two courses of treatment before surgery while our entire cohort was subjected to 3 cycles of treatment (24). In another study conducted by Shen et al, the pCR elicited by neoadjuvant PD-1 plus chemotherapy was 33%, which was exactly the same as ours (25). Actually, our study does differ from theirs.…”
supporting
confidence: 74%
“…Regarding pathological response, previous studies exhibited that an R0 resection rate was 96.3% and a pCR rate was 33.3% in patients with locally advanced ESCC receiving neoadjuvant nivolumab and pembrolizumab plus chemotherapy [ 9 ]. Likewise, in another study, pCR rate was 34.21%; meanwhile, R0 resection rate was 92.11% in locally advanced ESCC patients receiving neoadjuvant camrelizumab and pembrolizumab plus chemotherapy [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…PD-1 inhibitor, as a novel developed immune therapy, blocks the PD-1/PD-L1 linkage and has been widely applied in numerous carcinomas [ 12 , 14 ]. In addition, in locally advanced ESCC, nivolumab and pembrolizumab combination with chemotherapy was recently used for neoadjuvant therapy, which exhibited an acceptable therapeutic response, progression-free survival (PFS), and overall survival (OS) [ 9 ]. Camrelizumab, a domestic product developed in China, is a novel IgG4-kappa anti-PD-1 inhibitor that has been used for treatment of a variety of malignancies, such as refractory classical Hodgkin’s lymphoma and gastric or gastroesophageal junction adenocarcinoma [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although immunotherapy has showed promising results in advanced ESCC, however, the efficacy and safety of combination of PD-1 or PD-L1 with chemotherapy for locally ESCC. Recently, a retrospective analysis showed that neoadjuvant immunochemotherapy (nICT) for locally advanced ESCC has promising outcomes including: a high pathological complete response (pCR) rate (9/27, 33.3%), high microscopically margin-negative (R0) resection rate (26/27, 96.3%), and a low-toxicity profile (2/28, 7.1%, ≥ grade 3) (14). Based on the above compelling rationale, the role of PD-1 or PD-L1 inhibitors combined with chemotherapy in neoadjuvant treatment for locally advanced ESCC has gained much attention (e.g., NCT04654403, NCT04506138, NCT03946969, NCT04177797, NCT04280822).…”
Section: Introductionmentioning
confidence: 99%